Retinal toxicity of amphotericin B in vitrectomised versus non-vitrectomised eyes. Issue 9 (September 1986) - Baldinger, J; Doft, B H; Burns, S A; Johnson, B
Abstract : The retinal toxicity of intravitreally administered amphotericin B was compared in non-vitrectomised versus vitrectomised rabbit eyes. Doses of 5 and 10 micrograms in both groups resulted in transient vitritis but had no effect on electroretinograms. Histopathological examination four weeks after injection showed vitreous cells and minimal areas of retinal necrosis in both groups at 5 or 10 micrograms doses. At these doses vitrectomy did not modify the retinotoxic effects of intravitreally administered amphotericin B. At higher doses marked toxicity was found in both vitrectomised and non-vitrectomised groups.